(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Several IoT solutions have emerged as a result of the industry’s massive expansion. E-health has the potential to provide high-quality, accessible treatment. ’ It’s a challenge to keep the user ’s private medical file safe. Using a cryptography method, such as protecting personal data, is one option. In order to communicate information with several participants, each receiver must have their own unique encryption key (physicians, health agencies, etc.). Recompilation of the master password is required by one side of the (t, n) cutoff selective encryp tion mechanism for data exchange. This study presents a decentralized decoding method for PHR distribution that is successful. It’s simple to exchange information with others without having to reassemble the decoding pass word. We test the chosen-ciphertext safety of our tech nique. The JPBC package is used to execute our method on a PC. Our strategy seems to be viable and successful in ePHR, according on the results of our tests.